Enantioselective syntheses of tetrahydroquinolines based on iridium-catalyzed allylic substitutions: total syntheses of (+)-angustureine and (-)-cuspareine - Satyanarayana, Gedu; Pflästerer, Daniel; Helmchen, Günter (European journal of organic chemistry, 2011)
A protecting-group-free two-step approach for the preparation of tetrahydroquinolines has been developed. The procedure involves a highly regio- and enantioselective intermolecular iridium-catalyzed allylic amination followed by one-pot hydroboration and intramolecular Suzuki-Miyaura cross-coupling. This method was applied in total syntheses of the alkaloids (+)-angustureine and (-)-cuspareine.
Gesehen am 06.10.2022